STUDY OF FITNESS FOR SERVICE PIPELINE DUE TO PITTING CORROSION BASED ON API RP 579 - TRI WAHYUDI (NIM : 13105125); Pembimbing : Prof. Dr. Ir. IGN. Wiratmaja Puja, EKO
During operational mode, pipeline will directly contact with the working fluids and its environment. The corrosive chemicals can cause pipeline wall corroded and lead to the damage of the pipeline. Therefore, it is necessary to make evaluation for calculate the remaining strength, which called fitness for service. It related to follow up in the risk based inspection (RBI) to avoid failure or damage on the component. This final project conduct an analysis of fitness for service for pipeline due to pitting corrosion based on API RP 579. In order to ease analysis, writer has develop calculation sheet used to performing level 1 and level 2 assessment. As a case study, writer has performing fitness for service analysis for offshore pipeline Widuri DÃ‚Â–Widuri P with operating pressure 187.35 psi. From the available data, it was known that the uniform depth of pitting is 28% of pipe wall thickness. Analysis result indicates that the pipeline does not meet fitness for service acceptance criteria for level 1 and level 2. Remaining strength factor for level 1 assessment is 0.53 with reduced operating pressure 41%. Remaining strength factor for level 2 assessment is 0.61 with reduced operating pressure 32%. For the level 3 assessment results safety factor (SF) 0.84 with reduced operating pressure 16% for further operation.